Classroom Teacher Candidates’ Opinions Related to Using Drama in Primary School: An Example of Demirci Faculty of Education - Ümmühan ORMANCI; ŞAŞMAZ ÖREN Fatma (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi, 2010)
The classroom teacher candidates’ views are aimed to be determined for the use of drama in primary education in this study. The study group of this study consists of 58 classroom teacher candidates who are studying at Demirci the Faculty of Education. The research is a qualitative which consists of open-ended questions and semi-structured interview form. Data obtained from the study have been analyzed with the content analysis. According to the findings, teacher candidates have stated that drama classes which they had during university years will contribute to their careers and also drama is a funny lesson. Besides this, teacher candidates think that drama is available in primary classes. They have emphasized that using drama in primary education will provide with contribution for students to gain advantages such as empathy-building, creative and critical thinking, getting self-confidence, socialization, communicating,. Based on these results, it has been proposed that teacher candidates should be introduced drama and by making them applications for its usage, their knowledge and skills should be increased